SINERGITAS AKTOR KEPENTINGAN DALAM PENYELENGGARAAN PEMERINTAHAN DESA (Studi pada Desa Urek-Urek Kecamatan Gondanglegi Kabupaten Malang) - akbar pandu dwinugraha (Publisia: Jurnal Ilmu Administrasi Publik, 2017)
The village government in its implementation can not be alone carried out by the actors of village government but also needs to be assisted by other stake actors even though the village head becomes the main actor in building synergies with other stake actors with good results on the contrary. Descriptive research with qualitative approach is used in this study with the aim to analyze the synergy of interest actors in the administration of village government in Urek-Urek Village, Gondanglegi Sub-district, Malang Regency. Based on the analysis that has been conducted this research has resulted in the conclusion that among other things the communication that has been built, by the village government and other actors of interest has run well although the optimization especially communication by the village government together with women and poor groups which seems rarely done. Coordination that is built among actors of interest has also been running well although it is still deemed necessary made improvements including related aspects of direct relationships, preliminary planning and clear formulation of authority and responsibility.DOI: https://doi.org/10.26905/pjiap.v2i1.1421